PENGARUH RATE BAGI HASIL, BI RATE DAN INFLASI TERHADAP DANA PIHAK KETIGA PERBANKAN SYARIAH (STUDI PADA BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH YANG TERDAFTAR DI BANK INDONESIA TAHUN 2012 - 2015) - Veriansyah Veriansyah; Kamaliah Kamaliah; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study used a purposive sampling method or sampling based on criteria of course. The samples were Islamic banking, that is Sharia Commercial Bank(Bank Umum Syariah), and Sharia Business Unit(Unit Usaha Syariah). The method used in this study, namely multiple linear regression to analyze the effect of partial with SPSS version 20.0. From the results of testing that has been done partial test (t test) showed that the only variable in the BI Rate that has a strong influence on the Third Party Funds, while the Rate of Profit Sharing and Inflation does not have any effect on Deposits period January 2012 - December 2015. The amount of influence that caused (R2) by the three independent variables is jointly against variable dependenya at 79,7%, there maining 20,3% is influenced by other variables not included in the study.Keywords: Third Party Funds, Rate of Profit Sharing, BI Rate, and Inflation